The impact of rising interest rates on farm profitability and debt management strategies - Freund, Alexis M. (My University, 2025)
The agricultural sector depends on external financing, making it vulnerable to interest rate changes. This study examines the impact of rising interest rates on capital debt repayment capacity (CDRC) and default probability using Kansas Farm Management Association (KFMA) data. Sensitivity analysis reveals that while higher rates increase repayment costs, default risk is primarily driven by owner equity (OE) and working capital (WC). Farms with OE below 60% faced default probabilities exceeding 0.50%, while those above 80% had near-zero risk. A 50% reduction in WC significantly increased default probability, highlighting liquidity’s role in financial stability. Beyond financial metrics, lender-borrower relationships, risk management tools, and refinancing options influence farm financial resilience. Findings suggest that equity accumulation, liquidity preservation, and revenue diversification mitigate financial risk more effectively than focusing on interest rates alone. Policy interventions supporting credit access and debt restructuring may enhance financial stability. Future research should explore long-term refinancing risks, farm profitability under prolonged high-interest environments, and the effectiveness of financial education programs in improving borrower resilience. Additionally, the role of technological adoption in cost management and its potential to offset rising borrowing costs warrants further analysis. Understanding these dynamics can help lenders and policymakers implement targeted financial support mechanisms, ensuring the sustainability of agricultural operations in fluctuating economic conditions.
Keywords: Interest rate; Repayment capacity; Farm profitability; Debt management